From Erewhon to AlphaGo: for the sake of human dignity, should we destroy the machines?. Issue 1 (2nd January 2017) - Brownsword, Roger
ABSTRACT: This paper asks whether, for the sake of human dignity, regulators should adopt a precautionary approach to the development of smart machines. Having identified a set of essential (or commons') conditions for the existence of human social agents, including respect for human dignity in both foundational and non-foundational senses, consideration is given to human reliance on personal digital assistants, to the development of autonomous vehicles and lethal autonomous weapons systems, and to the use of smart machines in the criminal justice system. The paper concludes that, while smart machines should not be destroyed, a degree of precaution for the sake of human dignity is warranted. In particular, it is recommended that international agencies should monitor the impact of smart machines on the commons' conditions; and that national commissions should facilitate the articulation of the local social licence for the development and application of such machines.